2020
DOI: 10.1002/nau.24358
|View full text |Cite
|
Sign up to set email alerts
|

TVT‐O for treatment of pure urodynamic stress urinary incontinence: Efficacy and adverse effects at 13‐years follow‐up

Abstract: Aim To assess the efficacy and safety of tension‐free vaginal tape‐obturator (TVT‐O) 13 years after implantation for the treatment of female pure stress urinary incontinence (SUI). This is the longest‐term evaluation available of TVT‐O outcomes. Methods A multicenter, prospective study was conducted in five tertiary referral centers in three countries. All consecutive women with urodynamically proven pure SUI treated by TVT‐O were included. Data regarding subjective outcomes (International Consultation on Inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…The descriptive data were collected and anonymity was ensured by patient data encoding to confidential numbers in a rising pattern that were entered in an electronic worksheet. Perioperative complications were documented and classified by urology residents (investigators) based on the modified Clavien- Dindo grading system 18 as next described. Grade I: any deviation from the normal postoperative course without the need for pharmacological treatment or surgical, endoscopic, and radiological interventions; Grade II: requiring pharmacological treatment with drugs other than such allowed for grade I complications; Grade III: requiring surgical, endoscopic or radiological intervention; Grade IIIa: intervention not under general anesthesia; Grade IIIb: intervention under general anesthesia; Grade IV: life-threatening complication requiring intermediate/intensive care unit management; Grade IVa: single organ dysfunction (including dialysis); Grade IVb: multiorgan dysfunction; Grade V: death.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The descriptive data were collected and anonymity was ensured by patient data encoding to confidential numbers in a rising pattern that were entered in an electronic worksheet. Perioperative complications were documented and classified by urology residents (investigators) based on the modified Clavien- Dindo grading system 18 as next described. Grade I: any deviation from the normal postoperative course without the need for pharmacological treatment or surgical, endoscopic, and radiological interventions; Grade II: requiring pharmacological treatment with drugs other than such allowed for grade I complications; Grade III: requiring surgical, endoscopic or radiological intervention; Grade IIIa: intervention not under general anesthesia; Grade IIIb: intervention under general anesthesia; Grade IV: life-threatening complication requiring intermediate/intensive care unit management; Grade IVa: single organ dysfunction (including dialysis); Grade IVb: multiorgan dysfunction; Grade V: death.…”
Section: Methodsmentioning
confidence: 99%
“…When medial-to-lateral versus lateral-to-medial insertion transobturator techniques are compared, there is no evidence to support the use of one approach over the other 13 . However, reporting of longer-term results data in clinical trials is required 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…18 However, this decline in effectiveness over time was not observed by others. 8,9 These differences could be in part due to diverseness in success definitions and also owing to distinct characteristics of the cohorts such as studies that only included women with pure-SUI, without prior incontinence surgery or without POP. Nonetheless, long-term reoperation rate for SUI in the present cohort is similar to that described in a large population-based study.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] However, as TO-MUS were introduced more recently than retropubic slings 6 there are fewer data on their long-term effectiveness and safety. [7][8][9][10] It is of great importance to increase our knowledge of longlasting outcomes of implanted synthetic material because many women undergoing a MUS will live many years with the prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…TVT-O has been largely demonstrated as a highly effective and safe option for the treatment of female pure SUI. 14 However, the placement of mid-urethral slings has been associated with a number of perioperative and postoperative complications, including voiding dysfunctions, urinary retention, and de novo OAB symptoms. 15 Regarding the postoperative voiding dysfunction, Stanford et al reported an incidence of 16.3%.…”
Section: Discussionmentioning
confidence: 99%